A fractal-fractional gingerbread-man map generalized by p−fractal-fractional difference operator - R.W. Ibrahim; S. Momani (Қарағанды университетінің хабаршысы. Математика сериясы)
By using the generalization of the gamma function (p−gamma function: Γp(.)), we introduce a generalization of the fractal-fractional calculus which is called p−fractal-fractional calculus. Examples are illustrated including the basic power functions. As applications, we formulate the p−fractal-fractional difference operators. A class of maps, called gingerbread-man maps, is investigated. We present a new idea of a stability for continuous system, based on three parameters. Sufficient conditions are illustrated to obtain the stability of the system.